Decoding Gen Z: AI's influence on brand trust and purchasing behavior - Guerra-Tamez, Cristobal Rodolfo; Kraul Flores, Keila; Serna-Mendiburu, Gabriela Mariah; Chavelas Robles, David; Ibarra Cortés, Jorge (Frontiers in Artificial Intelligence, 2024)
This study focuses on the role of AI in shaping Generation Z's consumer behaviors across fashion, technology, beauty, and education sectors. Analyzing responses from 224 participants, our findings reveal that AI exposure, attitude towards AI, and AI accuracy perception significantly enhance brand trust, which in turn positively impacts purchasing decisions. Notably, flow experience acts as a mediator between brand trust and purchasing decisions. These insights underscore the critical role of AI in developing brand trust and influencing purchasing choices among Generation Z, offering valuable implications for marketers in an increasingly digital landscape.